Encapsulin carrier proteins for enhanced expression of antimicrobial peptides. Issue 3 (28th November 2019) - Lee, Tek‐Hyung; Carpenter, Timothy S.; D'haeseleer, Patrik; Savage, David F.; Yung, Mimi C.
Abstract: Antimicrobial peptides (AMPs) are regarded as attractive alternatives to conventional antibiotics, but their production in microbes remains challenging due to their inherent bactericidal nature. To address these limitations, we have developed a novel AMP fusion protein system based on an encapsulin nanocompartment protein and have demonstrated its utility in enhancing expression of HBCM2, an AMP with activity against Gram‐negative bacteria. Here, HBCM2 was fused to the N‐terminus of several Encapsulin monomer (Enc) variants engineered with multiple TEV protease recognition site insertions to facilitate proteolytic release of the fused HBCM2. Fusion of HBCM2 to the Enc variants, but not other common carrier proteins, enabled robust overexpression in Escherichia coli C43(DE3) cells. Interestingly, variants with a TEV site insertion following residue K71 in Enc exhibited the highest overexpression and HBCM2 release efficiencies compared to other variants but were deficient in cage formation. HBCM2 was purified from the highest expressing variant following TEV protease digestion and was found to be highly active in inhibiting E. coli growth (MIC = 5 μg/ml). Our study demonstrates the potential use of the Enc system to enhance expression of AMPs for biomanufacturing and therapeutic applications. Abstract : Antimicrobial peptides (AMPs) are regarded as attractive alternatives to conventional antibiotics, but their production in microbes remains challenging due to their inherent bactericidal nature. We have engineered a cage‐disrupted encapsulin carrier protein containing multiple TEV protease recognition sites. When fused to AMPs, this engineered encapsulin protein enabled robust AMP expression in Escherichia coli . In contrast to cage‐forming encapsulin proteins, release of AMP from the cage‐disrupted protein by TEV protease was highly efficient, ultimately yielding highly active AMP.